STRATEGI PENGEMBANGAN EKOWISATA KAWASAN MEMPURA KABUPATEN SIAK - Siregar, Sofyan Husein (Jurnal Kajian Lingkungan, 2013)
The study was conducted in Mempura region, Siak regency for 5 month, from July to November 2012. The aims of this study are: 1) to definite potential value of nature in Mempura region Siakregency; 2) to identify strength, weakness, opportunity and threat of Mempura region according to criteria of ecotourism, and 3) to define strategies for developing ecotourism in Mempura region. Descriptif methode is used in this study with SWOT analysis to take for certain development strategies of ecotourism based on area potencies result.Result of this study showed that: Mempura region has a great potentials for the development of ecotourism. It main source of attractions was the panorama/view of river, forest and durian garden. In addition, historical site and traditional culture activities provided additional attractions, as well as flora and fauna that varied in the region.Management strategies priority for ecotourism in the regionare : 1)increasing service and ease, 2)empowering regional planning aspect for ecotourism, 3)improvinghuman resources andecotourismfacility, 4) Involving local awareness andinisiative, 5)increasing promotion of ecoturism in Mempura region, 6) increasing monitoring activity in conservation of nature and local culture, and 7), involving management of ecotourism in Mempura region.Key word: Siak Regency, Mempura region, Ecotourism, Development strategy